Paleomagnetism of Carboniferous diabase dykes from Gaspé, Quebec - Seguin, Maurice K. (Canadian Journal of Earth Sciences, 1987)
The reported paleomagnetic study was carried out on 53 oriented samples (156 specimens) at 10 sites in the eastern Gaspé Peninsula. All sampled geological units are composed of sub vertical diabase dykes that cut the sedimentary formations of late Early Devonian – early Middle Devonian age. The radiogenic (whole-rock K/Ar) age of these and similar dykes ranges from Late Devonian to early Middle Carboniferous (mean whole rock K/Ar age = 310 Ma). Two components were isolated. The most common component, A (D = 152°, I = +41°), is normal, whereas the second component, B (D = 315°, I = −44°), is reverse. Both components may be considered as a single one; alternatively, component A may be considered slightly older than component B. Unblocking temperatures, median destructive fields, relative frequency of occurrence of the components, and various degrees of alteration are arguments favouring the first or the second situation. The case of a single component is more probable, representing an Early Carboniferous time of acquisition of remanence (thermoremanent magnetization (TRM) probably corresponding to the time of intrusion and resetting of surrounding sedimentary rocks). The corresponding paleopole position in 148°E, 11°N. This pole position is located some 25 °to the southeast of the cluster of Carboniferous poles (mainly Middle to Late Carboniferous) for the North American craton. The significance of this discrepancy is not well understood, but it is worth noting that very recent paleomagnetic results from western Newfoundland and central New Brunswick are located closer to the paleomagnetic results of this study. The age and direction of the dyke system suggest a short period of extension following the compressive pulse of the Acadian orogeny and preceding the Alleghenian orogeny. For these reasons, the dyke system is unrelated to the initial opening of the present Atlantic Ocean.